2009
DOI: 10.2337/dc09-0453
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between CarotidIntima-Media Thickness and Silent Cerebral Infarction in Japanese Subjects With Type 2 Diabetes

Abstract: OBJECTIVEWe examined the relationship between intima-media thickness of common carotid artery (CCA-IMT) and silent cerebral infarction (SCI) with the magnetic resonance imaging (MRI) study in Japanese subjects with type 2 diabetes.RESEARCH DESIGN AND METHODSThe brain MRI study and the carotid ultrasonography were performed in a total of 217 consecutive Japanese subjects with type 2 diabetes. Various risk factors for SCI were examined using multiple logistic analyses.RESULTSThe SCI was found in 60.4% of the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 14 publications
1
38
1
2
Order By: Relevance
“…Increased CCAIMT is a surrogate marker for atherosclerosis and SBI, and is a risk for stroke (29,30). Although CCAIMT was not significantly associated with SBI in the present study, the combination of baPWV!17.49 m/s and CCAIMT!1.1 mm strongly indicated the presence of SBI.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Increased CCAIMT is a surrogate marker for atherosclerosis and SBI, and is a risk for stroke (29,30). Although CCAIMT was not significantly associated with SBI in the present study, the combination of baPWV!17.49 m/s and CCAIMT!1.1 mm strongly indicated the presence of SBI.…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, because SBI required a diameter!3 mm, état cribIé was excluded. Nomura et al reported that CCAIMT, but not baPWV (by 1 cm/s) was independently associated with SBI in patients with diabetes mellitus (30). However, change the unit of pulse wave velocity (PWV) from cm/s to m/s might be better to identify the relationship of PWV with outcomes and to simplify determination of the cutoff values of PWV (4,27).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][12][13][14][15]21 age, hypertension and plaque score strongly and independently correlated with the occurrence of SCI of brain, compatible with results of other studies. 22,23,24 Conclusion Silent cerebral infarction (SCI) detected incidentally by MRI is considered the preliminary stage of accidental stroke and assumed to be secondary to atherosclerotic vascular disease (ASVD). Investigating its clinicopathology may elucidate the underlying mechanism of stroke onset and help to prevent this disabling disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they can directly stimulate or inhibit target gene transcription by directly binding to promoter regions, RNAactivation phenomena. miR-146a is involved in modulation of the inflammatory pathways in T2DM [6] Measurement of the carotid intima-media thickness (CIMT) has been recognized as a powerful method for identifying subclinical atherosclerosis, and increased thickness of the intima-media complex reflects local generalized atherosclerosis [7] .The objective of this study was to evaluate respective values of miRNA-146a and CHIT1andtheir association with CIMT, being a valid marker of atherosclerosis in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%